Stuff! : reduce, reuse, recycle - Kroll, Steven; Cox, Steve, 1961- (Tarrytown, NY : Marshall Cavendish Children, 2009)
Pinch is a pack rat who does not want to give up the possessions that are cluttering his house, but when he finally is persuaded to sell them at a neighborhood tag sale, he discovers the beauty of recycling. Includes tips on reducing, reusing, and recycling.
Booklist.
Kirkus Review.
1.6
K-3
Keywords: Animals -- Juvenile fiction; Garage sales -- Juvenile fiction; Neighborhoods -- Juvenile fiction; Rats -- Juvenile fiction; Recycling (Waste, etc.) -- Juvenile fiction; Waste products -- Juvenile fiction; Wood rats -- Juvenile fiction; Animals -- Fiction; Garage sales -- Fiction; Junk -- Fiction; Neighborhoods -- Fiction; Rats -- Fiction; Recycling (Waste) -- Fiction; Wood rats -- Fiction; Animals -- Fiction; Garage sales -- Fiction; Neighborhoods -- Fiction; Rats -- Fiction; Recycling -- Fiction; Waste products -- Fiction; Wood rats -- Fiction